SERVIÇOS FARMACÊUTICOS: AÇÕES DE GESTÃO NA LINHA DE CUIDADO MATERNO INFANTIL DE UM HOSPITAL UNIVERSITÁRIO - Sangoi, Salete Maria Girardi (2017)
The Unified Health System was created to carry out health promotion, prevention and recovery actions, obeying the principles of equality, universality and integral access to actions and services. The pharmaceutical professional is inserted in all levels of attention, that is, from primary care, specialized services and tertiary care. However, there is a gap in what refers to the performance of the pharmacist in the management of the health system. So that, this dissertation had as objective to enhance the integration and participation of the pharmaceutical professionals of the clinical analysis and hospital pharmacy services in the management of the Maternal Child Care Line of an University Hospital. Its specific objectives were: to present the main demands of the Maternal and Child Care Line for the pharmaceutical services linked to the laboratory of clinical analysis and hospital pharmacy of the institution; to discuss the result of prioritizing problems with managers of the clinical laboratory and hospital pharmacy and to elaborate informative material with the data collected, aiming to support the decision-making process by the management team of the Maternal Child Care Line. This work is justified by the need to promote greater integration of pharmacy professionals, as well as their recognition, of the importance of the performance of the pharmaceutical services in the management actions established for the Maternal and Child Care of the hospital. For that, a research-action methodology was developed, from November 2016 to May 2017. Ten of the health professionals who are part of the Line of Maternal Child Care participated in the research. Based on the data collected, the group's priorities were the resolvability of laboratory tests and the need for constant and permanent dialogue between the team. As a result, two articles were produced. The first one consists in a narrative review about the role of the pharmacist in tertiary services, whose objective was to get to know the recent literature on the subject and, based on it, to build a solid data base capable of subsidizing the discussion presented in this paper. The second, in turn, presents the demands of the pharmaceutical services of a university hospital, which were listed based on the empirical research developed. The product generated was informative material in a banner format, which was exposed in the meeting room of the Child Care Line of the team in order to give visibility to the priorities listed by the team.